UPTAKE RATE OF SULPHUR BY CANOLA PLANTS - MILLÉO, Marcos Vinícius Ribas; DONI FILHO, Luiz (Scientia Agraria, 2001)
This study was conducted in the field at the Universidade Estadual of Ponta Grossa (UEPG), Ponta Grossa, PR, during the 1994 and 1995 years. The uptake rate of sulphur by canola plants was determined as a function of their stage of growth under irrigated and non irrigated cropping. The demand for sulphur took place from the early stages up to full growth, and the nutrient was required nearly until the end of the cycle. It was found that the greatest need for sulphur occurred at the beginning of elongation, and by the time the first ten siliques were fully developed, the greatest accumulation of sulphur in the plant was observed. The period between the rosette stage and the beginning of flowering is the most indicated for the application of sulphur.